Enhanced passive safety surveillance of Influvac® and Influvac® Tetra: Results from seven consecutive seasons. Issue 2 (9th January 2023) - Moeller-Arendt, Melanie; van de Witte, Serge; Nauta, Jos; de Voogd, Hanka; Rogoll, Jutta; Nisslein, Thomas
Highlights: Enhanced Safety Surveillance for seasonal influenza vaccines is mandatory in EU since 2014/15. Data from Enhanced Passive Safety Surveillance for Influvac® and Influvac® Tetra are presented. Passive surveillance implemented for Influvac® & Influvac® Tetra complies with EU requirements. Results confirm the favourable safety profiles of Influvac® and Influvac® Tetra. Abstract: Background and objectives: In 2014, the European Medicines Agency (EMA) set out requirements for an enhanced safety surveillance for seasonal influenza vaccines. This paper presents data from the yearly Enhanced Passive Safety Surveillance (EPSS) implemented for Influvac® since season 2014/15 and continued for Influvac® Tetra from season 2018/19 onwards. Methods: In seven consecutive seasons, an EPSS, aiming for at least 1, 000 vaccinees (additional target of 100 vaccinees per five predefined age groups), was conducted in Germany, where market characteristics were expected to allow for a quick generation of representative data. Reactogenicity data in terms of reporting rates, severity and duration of pre-specified local and systemic adverse events of interest (AEI) were collected using response cards, which were completed by vaccinees and returned seven days after vaccination via regular mail. In addition, response cards contained a call center number to enhance reporting of other than pre-specified adverse events. Results: The primary target of at least 1, 000 vaccinees was surpassed in all seasons, as was the additional target of 100 adults and elderly. Reactogenicity data were in line with known safety profile of Influvac® and Influvac® Tetra. In children, the target was mostly met in seasons when the EPSS was conducted for Influvac®, but not in seasons when it was conducted for Influvac® Tetra. Although the data for Influvac® Tetra are based on a low number of paediatric vaccinees, they do not indicate a different reactogenicity profile of Influvac® Tetra compared with Influvac®. No signals were identified. Conclusion: The EPSS set up for Influvac® and Influvac® Tetra proved a robust and effective methodology to comply with the objectives of EMÁ's guidance on enhanced safety surveillance of seasonal influenza vaccines. Safety data from seven consecutive seasons confirmed the favourable safety profile of both vaccines.